Consumer debt non-payment and the borrowing constraint: Implications for consumer behavior - Bechlioulis, Alexandros P.; Brissimis, Sophocles N. (Journal of Banking & Finance, 2019)
This paper examines whether the consumption behavior of a borrowing-constrained household is affected by debt non-payment. From the household's intertemporal maximization problem, we derive a two-equation model consisting of augmented forms of the standard consumption Euler equation and the static labor supply equation. We estimate these equations by using nonlinear GMM and obtain estimates inter alia for the discount factor and the debt-payment-to-income ratio. The former is found to be much lower than the values often used in model calibrations in the literature, showing a high degree of impatience of households. The latter is close to the values reported in the consumer credit literature. Our results are found to be robust to a number of specification tests under different types of household preferences. These results are also subjected to a comparative analysis with the results derived from the consumption Euler equation under full debt repayment and no borrowing constraint.